Synthesis, characterization, optical, morphological, and antioxidant properties of oligo(2-ethoxy-6-(((2-hydroxyphenyl)imino)methyl)phenol) obtained by oxidative polycondensation - Kaya, Esin; Erdogan, Erman; Bursal, Ercan; Canpolat, Erdal (Springer, 2021)
A newly designed oligo-Schiff-base was prepared and characterized to investigate its optical and morphological response and antioxidant activity. We first clarified the synthesis of 2-ethoxy-6-(((2-hydroxyphenyl)imino)methyl)phenol (EHPIMP) from the condensation reaction of 3-ethoxy-2-hydroxybenzaldehyde with 2-aminophenol. The subsequent oxidative polycondensation process yielded the target oligo(2-ethoxy-6-(((2-hydroxyphenyl)imino)-methyl)phenol), oligo (EHPIMP). The structural elucidation of oligo (EHPIMP) was performed by H-1, C-13 NMR, TGA, FTIR and GPC systems. The optical properties of the EHPIMP and the oligo (EHPIMP)'s thin films were compared mainly with UV-Vis spectroscopy. Corresponding band gap (E-g) values of the EHPIMP and the oligo (EHPIMP) films were obtained as 2.224 and 1.404 eV, respectively. 2D and 3D surface images of films were analyzed with atomic force microscopy. In the AFM results, the surface roughness values and the average roughness were attained to be 8.28 nm and 46.63 nm for EHPIMP and the oligo (EHPIMP)'s thin films, respectively. Furthermore, the antioxidant activities were investigated using in vitro FRAP, CUPRAC, DPPH, and ABTS methods. The obtained data demonstrated that EHPIMP and oligo (EHPIMP) had effective reducing antioxidant potentials and radical scavenging activities.
Keywords: Organic semiconductor; Poly-Schiff-base; Optical band gap; Morphology; Antioxidant; Radical scavenging; Thin films